(untitled) (Bangladesh Journal of Agriculture, 2023)
BARI solar cabinet dryer was tested with the moist radish ( about 9 kg) at Hill Agricultural Research Station (BARI), Khagrachari, during 17-18 February 2020. Drying temperature, relative humidity, air velocity, and solar radiation were recorded. After drying, the final weight of the radish was 554 g (93.84% reduction). The inside air temperature of the drying chamber varied from 45.5 to 52.5°C (first day) and 47.44 to 52.5°C (second day). Air relative humidity in the drying chamber varied from 13.2 to 20.25% (first day) and 11.5 to 18.5% (second day), whereas the relative humidity in the ambient varied from 30.5 to 67.5 % (first day), and 42.3 to 65.3% (second day). Solar radiation varied from 50 to 900 W/m2 during the testing period. Moist radish dried in the dryer attained final moisture content of 9.0% from an initial moisture content of 94% after 11 hours of drying period whereas, it took 56 hours to reduce the moisture content to 12% (wb) of a similar sample in the open sun. In the open sun drying method, 9.0 kg of moist radish was dried to 380 g (95.8% reduction). In the open sun drying method, radish losses by 30% during drying because of fungal spoilage. The color of dried slices in the dryer was more bright and the smell was good compared to sun drying of radish slices. The dryer maintained nutrition and made hygienic and safe products of radish slices. Hilly farmers and small-scale traders would be benefitted from using the BARI solar cabinet dryer. Bangladesh J. Agri. 2023, 48(1): 1-9